Sequence-switch coding for low-power data transmission. - Myungchul Yoon (IEEE Transactions on VLSI systems)
Reducing the power dissipated by buses becomes one of the most important elements in low-power VLSI design. A new coding scheme called sequence-switch coding (SSC) is proposed in this paper. It is a general-purpose coding scheme that employs the sequence of data in reducing the number of transitions on buses. A simple switching algorithm is presented to show the feasibility of SSC. According to simulations, this algorithm reduces around 10% of bus transitions in the transmission of benchmark files. SSC can be used for burst data transfer in any application. In particular, it is suitable for internet and multimedia applications that have stream-type data transfer pattern.